2021
DOI: 10.1186/s12888-021-03449-y
|View full text |Cite
|
Sign up to set email alerts
|

Risk and protective factors of depression in the general population during the COVID-19 epidemic in Korea

Abstract: Background The risk of depression has risen in the general population during the COVID-19 epidemic. This study was conducted to explore risk and protective factors associated with depression among the general population uninfected by COVID-19. Methods A cross-sectional study was conducted with 1,500 representative South Korean citizens aged 19–65 years through an anonymous online survey. Depression was defined as a Patient Health Questionnaire-9 sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 53 publications
0
27
1
Order By: Relevance
“…18,77 In particular, our previous study of the general adult population showed that gratitude significantly protected against depression during the pandemic. 31 Gratitude might enhance people's coping resources and emotional well-being in the face of negative events. 78,79 In a study of American adolescents conducted during school closures due to the COVID-19 pandemic, "secondary engagement" coping mechanisms, such as gratitude, were associated with persistent positive emotions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,77 In particular, our previous study of the general adult population showed that gratitude significantly protected against depression during the pandemic. 31 Gratitude might enhance people's coping resources and emotional well-being in the face of negative events. 78,79 In a study of American adolescents conducted during school closures due to the COVID-19 pandemic, "secondary engagement" coping mechanisms, such as gratitude, were associated with persistent positive emotions.…”
Section: Discussionmentioning
confidence: 99%
“…Gratitude was measured using the Korean version of the Gratitude Questionnaire-6 (K-GQ-6) adapted by Kwon et al 30 The K-GQ-6 items were scored based on intensity using a 7-point Likert scale ranging from 1 (strongly disagree) to 7 (strongly agree), with higher scores indicating a more grateful attitude and more positive emotions. 31 We analyzed total scores and the internal consistency was acceptable (Cronbach's α=0.703).…”
Section: Gratitudementioning
confidence: 99%
“…115 Earlier studies of the Korean population showed that regular activity is a protective factor against depression and suicidal ideation. 116,117…”
Section: Regulated and Healthy Lifestylementioning
confidence: 99%
“…Gratitude is a well-known concept in the field of positive psychology, and people with high levels of gratitude can find positive aspects even in negative situations and reinterpret events ( 26 ). Individuals with a lot of gratitude are highly satisfied with their lives, frequently experience optimistic or positive emotions, and have lower levels of depression and stress ( 27 , 28 ). In studies related to COVID-19, gratitude were positively associated with mental wellbeing during the lockdown in the United Kingdom ( 29 ).…”
Section: Introductionmentioning
confidence: 99%